Comparison of body fat assessment methods on field in elite junior rowers - Kelso, A.; Trajer, E.; Machus, K.; Treff, G.; Müller, W.; Steinacker, J. M. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: There is a large variety of body fat measurements, which differ in validity and reliability, especially for athletes. It is necessary to find a method that quantifies body fat most accurately and that is feasible for field testing. The purpose of this study was to compare three methods of body fat estimation in rowers of the German National Junior Rowing Team (8 females, 8 males): skinfold-thickness (SKF), near-infrared interactance (NIR) and ultrasound (US) measurement of subcutaneous adipose tissue (SAT). Methods: The examiners were certified by the International Society for the Advancement of Kinanthropometry (ISAK) and Association of Applied Sciences in Medicine and Sports (ASMS). SKF and NRI measurements were taken at three sites and are reported as total body fat percentage (BF%). US measurements were taken at 8 sites and are reported as a sum of SAT (mm) with a distinction made between SUMExcl (without embedded structures) and SUMIncl (including embedded tissues) (10/15 MHz linear transducer L12-3 US, Phillips CX50, Amsterdam, NL). Results: Mean BF% via SKF was 10.9 ± 1.9% and 11.7 ± 2.9% via NIR. Mean SAT thickness was 46.6 ± 12.1mm (SUMIncl), respectively 42.5 ± 11.4mm (SUMExcl). A comparison of the three body fat assessment measurements showed significant correlations between US and SKF (SUMIncl: p<0.001, r2=0.86; SUMExcl: p<0.001, r2=0.86) and between US and NIR (SUMIncl: p<0.01, r2=0.38; SUMExcl: p<0.01, r2=0.40). There were also significant correlations between SKF and NIR (p<0.001, r2=0.56). Furthermore, a Bland-Altman-analysis showed a 95% agreement between the SKF and NRI method. Discussion: Body fat assessment in field testing can be performed by using any of these three methods. US allows the quantification of pure SAT, and the protocol for fat patterning by Müller et al. (2016) permits reliable and valid results. Currently there are no reference data and/or a formula for estimating US-BF (%), and further research is required. The SKF method cannot quantify pure SAT, and NIR has lower accuracy compared to US and SKF. The method of choice depends on the skills of the examiner, number of athletes and available time. For highly accurate SAT measurements, US could be a gold standard once reference data is established.